Hubungan Peran Keluarga dan Tingkat Pengetahuan Lansia tentang Personal Hygiene - Purnamasari, Oktika Ratna; Handayani, Ayu Mustika (Jurnal Akademika Baiturrahim Jambi, 2024)
Based on data from the elderly population in Indonesia, it is estimated that almost 68% of the elderly experience poor personal hygiene, the elderly are unable to meet their personal hygiene needs. Prevalence of diseases caused by personal hygiene: Skin diseases. There were 122,076 cases of skin disorders in Indonesia. According to data from the Jambi Provincial Statistics Agency of the 10 most common diseases in Jambi province, including leprosy and diarrhea. The aim of this research is to determine the relationship between family roles and the level of knowledge of the elderly regarding personal hygiene in Tangkit Village, Sungai Gelam District. This research is a quantitative research with a cross-sectional research design with a sample size of 33 respondents and using the Chis-Square test. Based on the research results, there is a relationship between the role of the family and personal hygiene and there is a relationship between the level of knowledge and personal hygiene carried out in Tangkit Village, Kec. Gelam River with statistical test results obtained p-value=0.020 (<0.05). Suggestions for families who have elderly relatives to increase their role towards the elderly to be able to have a positive effect on the Personal Hygiene of the elderly and to be able to actively participate in posyandu for the elderly